PENINGKATAN LITERASI LAKTASI MELALUI PELATIHAN PEER-COUNSELOR PADA KOMUNITAS PENDUKUNG ASI LACTALOVER - Azniah Syam; Hasifah Hasifah (Politeknik Negeri Sriwijaya, 2020)
One effort to improve breastfeeding promotion program recommended by WHO is to encourage the formation of breastfeeding peer-support groups. The best Peer-Support are people who are close to the life of the mother, who have a high and homogeneous intensity of interaction. The Community Service Program working together with Lactalover Breastfeeding Peer-Support Group, which consists of a household mother, will develop the Breastfeeding literacy program. This activity is gradual, starting with the training of peer lactation counselors aimed at increasing breastfeeding activities and breaking down the barriers to access to correct information around the practice. This community service activity proved to increase the capacity of homemakers, especially nursing mothers, to strengthen their role in supporting lactation literacy efforts. Peer-counselor training can overcome the obstacles of distance, time, and place for nursing mothers to get the information needed when facing obstacles in breastfeeding..